The JSE/BESA merger : navigating the integration minefield - Bowen, Amanda; Ngoma, Wendy ([London] : SAGE, 2016)
A few days before the JSE Limited (JSE) and the Bond Exchange of South Africa Limited (BESA) merged in June 2009, Nicky Newton-King, deputy CEO of the JSE - who had been tasked with leading the integration of the two organisations - reviewed what she had done so far and the plans she had put in place to ensure a smooth integration. A great deal of time and work had been invested in planning and organising the merger, and she did not want a misstep in the integration process to derail the entire merger. She wondered if she had done enough to ensure a smooth integration.
Originally Published in: Bowen, A., & Ngoma, W. (2010). The JSE/BESA Merger: Navigating the Integration Minefield. WBS-2010-13. Johannesburg: The Case Centre, Wits Business School.
Description based on online resource; title from home page (viewed on April 26, 2016).
Keywords: elektronické knihy; electronic books; JSE Limited; Bond Exchange of South Africa Limited; Organizational change -- Case studies; Consolidation and merger of corporations -- Case studies